1980
DOI: 10.4141/cjps80-061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seed- And Soil-Applied Rhizobium Japonicum Inoculants on Soybeans in Ontario

Abstract: . 1980. Effects of seed-and soil-applied Rhizobium japonicum inoculants on soybeans in Ontario. Can. J. Plant Soybeans (Glycine max (L.) Merrill), inoculated with 1.75 kg/ha of seed-applied inoculant (Rhizobium japonicum (Kirchner) Buchanan) or 40 kg/ha of granular, soil-applied inoculant, were grown in 1976 and 19'77 , along with uninoculated control plots, in fields planted to soybeans for the first time. Control plots averaged 2.1 tlha, compared to 2.6 tlha for the seed-applied inoculant and 3.1 t/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 5 publications
1
17
1
Order By: Relevance
“…Seed yields in all years were not different between the SG and SL inoculants, but yields for the SP were higher than (Bezdicek et al 1978;Muldoon et al 1980) and faba bean (Vicia faba L.) (Dean and Clark 1977). We cannot explain the relatively low yield for the SG inoculant because the same chickpea cultivar and mesorhizobial strains were used with success in other field experiments in which SG treatments typically were superior or as good as all other treatments (KyeiBoahen et al 2002a).…”
Section: Seed Yield and Seed Protein Concentrationmentioning
confidence: 84%
“…Seed yields in all years were not different between the SG and SL inoculants, but yields for the SP were higher than (Bezdicek et al 1978;Muldoon et al 1980) and faba bean (Vicia faba L.) (Dean and Clark 1977). We cannot explain the relatively low yield for the SG inoculant because the same chickpea cultivar and mesorhizobial strains were used with success in other field experiments in which SG treatments typically were superior or as good as all other treatments (KyeiBoahen et al 2002a).…”
Section: Seed Yield and Seed Protein Concentrationmentioning
confidence: 84%
“…In Canada, this has also been demonstrated in alfalfa , faba beans (Dean and Clark 1977) and soybean (Muldoon et al 1980). Hynes et al (1995) found no significant differences in pea nodulation and grain yields between liquid and peat seed inoculation, but soil inoculation was not investigated.…”
mentioning
confidence: 85%
“…These methods are often better and never worse than conventional seed inoculation for initiating nodulation and N2 fixation (e.g. Brockwell et al, 1980;Chamber, 1983;Danso et al, 1990a;Hale, 1981;Jensen, 1987;Muldoon et al, 1980;Rice and Olsen, 1992). Solid inoculant may be introduced into the seed bed through an insecticide attachment to the seed drill.…”
Section: Application Of Inoculantmentioning
confidence: 99%